Implementation of PBL Model in Improving Student Learning Outcomes on Noble Morals Material at SD Negeri 105413 Pergulaan - Aminah, Lutik; Rusnani; Jumiah; Ratnawati; Badariyah (MANDAILING GLOBAL EDUKASIA, 2025)
Education plays an important role in shaping the character of students, especially in instilling noble moral values. However, learning noble morals is often less effective if it only uses the lecture method without actively involving students. The Problem-Based Learning (PBL) model is one of the innovative approaches that can improve student learning outcomes in understanding and applying noble moral values. This study aims to analyze the effectiveness of implementing the PBL model in improving the learning outcomes of grade IV students on the material of noble morals. The implementation of PBL is carried out through several stages, namely problem identification, information exploration, discussion and analysis, presentation of results, and reflection and conclusions. This model helps students understand the concept of noble morals through real situations, improves their critical thinking skills, communication, and learning motivation. The results of the study showed that the implementation of PBL can make learning more interesting, meaningful, and increase student involvement. With this method, students are more active in finding solutions to the problems given, so that their understanding of the material is deeper. Therefore, the PBL model is recommended as an effective learning strategy in improving student learning outcomes on the material of noble morals